2003
DOI: 10.1067/mtc.2003.73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes on early and late survival after isolated first coronary bypass surgery in multivessel disease

Abstract: Diabetes is an independent risk factor for early cardiac death only. Long-term survival in patients who survive the first 30 days is not statistically significantly different for diabetic and nondiabetic patients. In fact, the rates appear very similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 34 publications
3
45
2
3
Order By: Relevance
“…14 However, long-term survival of patients with diabetes after cardiac surgery has been less extensively studied and remains controversial. [15][16][17] In the present study, a large, unicenter regional database with 100% follow-up was used to examine longterm cardiac-specific survival, because cardiac death is the most frequent cause of death in patients with diabetes undergoing CABG surgery. 18 Our findings reveal that NIDDM is not an independent risk factor for long-term cardiac-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, long-term survival of patients with diabetes after cardiac surgery has been less extensively studied and remains controversial. [15][16][17] In the present study, a large, unicenter regional database with 100% follow-up was used to examine longterm cardiac-specific survival, because cardiac death is the most frequent cause of death in patients with diabetes undergoing CABG surgery. 18 Our findings reveal that NIDDM is not an independent risk factor for long-term cardiac-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients are 2 to 3 times more likely to develop CHD, and experience worse clinical outcomes following an acute myocardial infarction, [1][2][3] coronary angioplasty, 4 and cardiac bypass surgery. [5][6][7] The reason for the worsened cardiovascular outcomes in diabetic patients is currently unclear. Preclinical animal studies suggest that there may be specific defects in diabetic cardiomyocytes which may be responsible including increased mitochondrial generation of reactive oxygen species, downregulation of the PI3-Akt survival kinase pathway, and reduced rates of adenosine triphosphate (ATP) synthesis (reviewed in refs [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports on survival of patients with chronic dialysis after CABG 4,[15][16][17][18][19][20][21][22][23][24][25][26] have demonstrates the operation can be performed with an acceptable mortality and morbidity for dialysis patients. 16,17,19,23,24,26 Herzog et al reported that dialysis patients have better long-term survival after CABG surgery than after percutaneous coronary intervention, especially diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to The United Kingdom Prospective Diabetes Study (2003), the largest-scale prospective study of diabetic nephropathy, when serum creatinine levels increase over 2.0 mg/dl, renal failure becomes end-stage, which requires dialysis within approximately 2.5 years and at which point the patient is likely to die within 3 years, 3 with the major cause of death being cardiovascular disease. 4,5 We mainly perform OPCAB in chronic dialysis patients and their intraoperative management has been established with an acceptable clinical outcome. In the present study, we investigated the preoperative and intraoperative confounding factors for chronic dialysis patients who underwent OPCAB and we assessed the impact of diabetic nephropathy and other possible risk factors on midterm survival after OPCAB in this population.…”
mentioning
confidence: 99%